Perbandingan Pengukuran Kadar Vitamin C Menggunakan Spektrofotometri UV-Vis pada Panjang Gelombang UV dan Visible - Khoirul Ngibad; Dheasy Herawati (Borneo Journal of Medical Laboratory Technology, 2019)
Vitamin C is a source of antioxidants which has a primary function to inhibit the occurrence of an oxidation reaction and inhibit a free radical. The source of vitamin C can be found in food and beverage. This study aims to compare the measurement of vitamin C levels using a UV-Vis spectrophotometer at UV and Visible wavelength. The method used in this study was the UV-Vis spectrophotometry method. The analysis of vitamin C levels at UV wavelength 266 nm and Visible wavelength 494 nm with a calibration curve range 0.3 to 0.8 mg/L. Validation of the methods studied included: linearity, detection limits, quantization limits, and precision. The results showed that the measurement of vitamin C levels at UV wavelengths resulted in the linearity of concentrations of 0.2 - 0.8 mg / L, the limit of detection of 0.05 mg/L, the limit of quantization of 0.17 mg/L and level of precision with RSD to 0.2015. On the other hand, the measurement of vitamin C levels in the Visible wavelength produced linearity from concentrations of 0.3 to 0.8 mg/L, the detection limit of 0.05 mg/L, quantization limit of 0.18 mg/L and the level of precision with RSD of 1.0489. Thus, the determination of vitamin C levels in samples using a UV-Vis spectrophotometer was preferred to be measured at UV wavelengths.